System Identification Using Group Method of Data Handling (GMDH) - Abu-Kheil, Yasmeen Mohammed Zuhair (2009)
A Master of Science Thesis in Mechatronics Submitted by Yasmeen Mohammed Zuhair Abu-Kheil Entitled, "System Identification Using Group Method of Data Handling (GMDH)," January 2009. Available are both Soft and Hard Copies of the Thesis.